The film ’Hollow city’ - an adaptation of the book ’The adventures of Ngunga’: from utopia to dystopia - Lauriti, Thiago (Literartes, 2022)
This article seeks to identify the “new lenses and discourses” that mark the film Hollow city, from 2004, by the Angolan filmmaker Maria João Ganga, in relation to the text that serves as a source for Ngunga’s adventures, by 1972, by fellow Angolan artist Artur Carlos Maurício Pestana dos Santos, known as Pepetela. For this purpose, studies by Robert Stam (2006) and Linda Hutcheon (2011) on adaptation will be used as theoretical and analytical contributions. Both explore the intertextual or dialogical possibilities that are established when a literary work is adapted for the cinema, transporting local particularities to other space-times that result in a new, hybrid work and not necessarily inferior to the one that gave rise to it. Both move away from the rhetoric of loss that laments what was lost in the transition from novel to film.